2022
DOI: 10.3390/ijerph19010480
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression Detection via Deep Sequence Learning of Successive Radiographic Scans

Abstract: The highly rapid spread of the current pandemic has quickly overwhelmed hospitals all over the world and motivated extensive research to address a wide range of emerging problems. The unforeseen influx of COVID-19 patients to hospitals has made it inevitable to deploy a rapid and accurate triage system, monitor progression, and predict patients at higher risk of deterioration in order to make informed decisions regarding hospital resource management. Disease detection in radiographic scans, severity estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“… [ 37 ] Proposed ensemble learning techniques for detecting pneumoconiosis disease in CXRs using multiple deep learning models Chest X-ray radiographs (CXRs) Deep ensemble learning NA The ensemble framework outperformed others, achieving an accuracy of 91.50% in the automated detection of pneumoconiosis. Although, the ensemble learning techniques shown an improved performance but there is need for potential techniques to help radiologists in the primary screening of pandemic [ 8 ] A deep sequence learning-based technique to forecast improvement or worsening in subsequent chest X-ray scans using those scans was proposed A lung disease and OVID chest X-ray datasets were used DCNNs NA Among DCNNs feature extractors used, ChexNet (DenseNet121) PT outperformed others with Precision, recall, F-measure and AUC of 0.921, 0.918, 0.920, and 0.92 respectively The accuracy of the prediction was not reported and other state-of-the-art metrics reported might be improved when optimization techniques or feature selection algorithm is introduced [ 44 ] The goal was to develop an uncertainty-aware CNN model for prediction of COVID-19 COVID19CXr, X-ray image, and Kaggle datasets UA-ConvNet EfficientNet-B3 model and Monte Carlo (MC) dropout The suggested UA-ConvNet model achieves sensitivity of 98.15% and G-mean of 98.02% (with a Confidence Interval of 97.99–98.07). The method demonstrated its superiority over the currently used techniques for identifying COVID-19 instances from CXR images.…”
Section: Results and Analysismentioning
confidence: 99%
“… [ 37 ] Proposed ensemble learning techniques for detecting pneumoconiosis disease in CXRs using multiple deep learning models Chest X-ray radiographs (CXRs) Deep ensemble learning NA The ensemble framework outperformed others, achieving an accuracy of 91.50% in the automated detection of pneumoconiosis. Although, the ensemble learning techniques shown an improved performance but there is need for potential techniques to help radiologists in the primary screening of pandemic [ 8 ] A deep sequence learning-based technique to forecast improvement or worsening in subsequent chest X-ray scans using those scans was proposed A lung disease and OVID chest X-ray datasets were used DCNNs NA Among DCNNs feature extractors used, ChexNet (DenseNet121) PT outperformed others with Precision, recall, F-measure and AUC of 0.921, 0.918, 0.920, and 0.92 respectively The accuracy of the prediction was not reported and other state-of-the-art metrics reported might be improved when optimization techniques or feature selection algorithm is introduced [ 44 ] The goal was to develop an uncertainty-aware CNN model for prediction of COVID-19 COVID19CXr, X-ray image, and Kaggle datasets UA-ConvNet EfficientNet-B3 model and Monte Carlo (MC) dropout The suggested UA-ConvNet model achieves sensitivity of 98.15% and G-mean of 98.02% (with a Confidence Interval of 97.99–98.07). The method demonstrated its superiority over the currently used techniques for identifying COVID-19 instances from CXR images.…”
Section: Results and Analysismentioning
confidence: 99%
“…For each gene, we also calculated the number of individuals carrying variants in any given gene. The top-ranked genes are KRAS (22), TP53 (17), KMT2C (17), LRP1B (14), FGFR2 (13), RGPD3 (11), EWSR1 (10), and RGPD4 (10) (Supplementary Table S2).…”
Section: Somatic Single-nucleotide Variants (Snvs)mentioning
confidence: 99%
“…This degree of heterogeneity has previously been underestimated or understated in the literature and in studies that undertake the discovery of biomarkers related to disease progression. It is also reflected by the results of population-based DNA sequencing and RNA expression studies to date, in that no consistent pattern of mutations or RNA expression profiles have yet been defined that accurately predict biological aspects of disease progression 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 pandemic in late 2019 and early 2020, it has been found that chest radiography imaging can be effectively used to observe and summarize lung abnormalities, including ground glass opacities and their distribution in both lungs. Extensive studies on CXR imaging have shown their potential for severity assessment on the basis of lung involvement in the infection, disease progression detection [ 6 ], and prognosis prediction. However, in the case of COVID-19, the novelty of the disease makes it more challenging even for the expert radiologists to confidently interpret the findings, particularly on CXRs [ 12 , 13 , 14 ].…”
Section: Related Workmentioning
confidence: 99%
“…Though CT represents 3D volumetric data, CXRs provide many advantages, such as quick triaging, availability, accessibility, and portability. In recent years, CXRs have been used extensively by researchers to develop deep-learning methods for COVID-19 detection [ 5 ], progression detection [ 6 ], severity estimation [ 7 ], and prognosis prediction [ 8 ]. Most studies focus on training end-to-end deep learning models to predict COVID-19 progression or outcomes from CXRs [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%